Wealth, trade and the environment: Carrying capacity, economic performance and wellbeing in Brazil and Italy - Pereira, Lucas; Zucaro, Amalia; Ortega, Enrique; Ulgiati, Sergio (Journal of Environmental Accounting and Management, 2026)
Time series analyses have been proven to be useful in capturing tendencies of country’s economical behavior. The aim of this work is to investigate and compare time series of Brazilian and Italian economies on the basis of the emergy synthesis method. The main objective is to provide comprehensive indicators of carrying capacity, economic performance and wellbeing over time, pointing out the differences between a fast developing nation, Brazil, and a developed nation, Italy. Focus is placed on emergy indicators capable of accounting for societal metabolism and shedding light on conventional monetary assessments. Trade between Brazil and Italy is also investigated in order to stress issues of fair and equitable trade in terms of balanced emergy exchange. Emergy indicators show that Brazil now relies on a decreasing percentage of renewable resources, resulting in increasing environmental load and decreasing global sustainability. Results are even worse for Italy that keeps using much larger fractions of nonrenewable and imported resources. As for the trade between the two countries: in the year 2008, Brazil exported to Italy 5.68E+22 seJ mainly in the form of raw resources, while imported 1.78E+21 seJ of manufactured commodities, generating a huge unbalance in terms of emergy traded.